Nutritional status and muscle function in Chilean adolescents according to the vulnerability index - Castro Cisterna, Silvia Ivonne.; Ochoa Araya, Silvia Inés.; Amoretti Arévalo, Enzo Patricio Daniel. (Federación Española de Docentes de Educación Física, 2024)
Introduction: Socioeconomic level evaluated in various ways has been a factor that has consistently been associated with physical activity and obesity levels. Chile has presented social changes in recent years, influencing the level of vulnerability of children and adolescents, this level is determined through the vulnerability index (IVE). The objective of this study is to analyze differences in nutritional status and muscle function according to the IVE, in 15-year-old students from educational establishments in communes of the Metropolitan region of Chile. Method: 91 15-year-old schoolchildren were evaluated (51 men and 40 women), belonging to 2 educational establishments, characterized by IVE (IVE-0 and IVE-89). The anthropometric variables measured were weight, height, waist circumference, BMI and Z-score-BMI were calculated and muscle function was measured by grip strength (kg) and lower body explosive strength (cm). Results: Significant differences were observed by IVE in Zscore-BMI [IVE-0: 0.71 (0.48-1.29) IVE-89: 1.32 (0.2-2.85) (p<0. 0001)] and grip strength (kg) [IVE-0: 36.6 (26-37.7) IVE-89: 32.4 (25.5-37.2) (p<0.0001)] in 15-year-old schoolchildren. Conclusions: There is a higher prevalence of overweight and obesity, as well as lower muscle function, in adolescents belonging to establishments with a higher vulnerability index (IVE 89).
Estado nutricional y función muscular en adolescentes chilenos de acuerdo con el índice de vulnerabilidad
Keywords: Muscle function; Nutritional condition; Socioeconomic level; Vulnerability index; Adolescentes